Crosslinking density of silk fibroin - Rice starch hydrogels modified with trisodium trimetaphosphate - Anucha Racksanti (2018)
Silk fibroin (SF) and rice starch (RS) are both biopolymers being non-toxic, biocompatible and biodegradable which can be utilized as hydrogels. The aim of this study was to prepare the SF-RS hydrogels modified with trisodium trimetaphosphate (STMP) and determine its crosslinking density for providing a guideline for preparing better quality absorbable hydrogels. The SF-RS hydrogels modified with various percentages of STMP were prepared by solution casting at pH 12 then neutralized to pH 7. The functional groups and molecular linkages of the hydrogels were investigated by Fourier transform infrared spectrometry (FTIR) and proton nuclear magnetic resonance ( 1 H NMR) spectrometry, respectively. Finally, the crosslinking density of the hydrogels was determined by UV/Vis spectrophotometry via the measurement of the relative amount of methylene blue (RMB) bound to the hydrogels. Results from the FTIR and 1 H NMR spectra revealed that linkages within the hydrogels occurred mainly between the O-H groups of RS and the triphosphate groups of STMP. From the MB adsorption study, the crosslinking density of the SF-RS hydrogel with 1.0%w/w STMP at the 60 min saturation time was approximately 63%. © (2014) Trans Tech Publications, Switzerland.